A função educativa do serviço social: espaço de "Educar-a-Ação" - Bruno, Tatiana de Fátima Domingues (2009)
This discourse is about the understanding of the Social Service educational function in your performance in PAIF - Programa de Atenção Integral às Famílias in Santo André municipal district. From the understanding of the pedagogies, study developed by Abreu (2002) in the Social Service ambit and contextualization of the Social Service as profession instituted to ease the conflicts between capital and work, contextualizing, from your genesis to the current days. The study sent the organization of the culture in your different manifestations in which the social assistant is also inserted, understanding your work with important characteristic in the organization and manifestation of the culture. However, the intentionality of the professional action is determined if the professional is an organic intellectual committed with the subordinate classes or it is committed with the interests of the dominant block, still apprehending, the existent contradictory movement in these mediations. This survey had for base the analysis of primary and secondary data, collected for more than an investigation instrument, as interview semi-structured with the managers of PAIF in Santo André and focal group with the social assistant involved in the program, besides bibliographical and survey documental. It can be ended that the educational process / pedagogic it is unmasked in the daily professional as manifestation of the apprehensions ethical-politicize and theoretical-methodological for the professional with your relation with the ethical-political project chosen by the professional category. More than to educate the other, which points is continually a space of professional Educate-to-action for the social worker